CONSTRUCTING AN ETHICAL MODEL FOR PERSONAL BRANDING: A THEMATIC ANALYSIS OF THE QUR’ANIC CONCEPT OF REPUTATION - juneni ijun; Muhammad Alif; Miskah (Hikami : Jurnal Ilmu Alquran dan Tafsir, 2026)
The emergence of modern digital self-imaging (the phenomenon of digital personal branding) is generally framed within a secular-pragmatic paradigm that views reputation primarily as the simulated management of one’s image in pursuit of cyber metrics. This study aims to deconstruct this model by developing a new theory of reputation based on sacred texts through a thematic analysis of verses from the Qur'an. This study employs an exploratory descriptive qualitative approach using a systematic content analysis design that examines a corpus of 23 Qur’anic verses obtained from the analyzed manuscripts and processed through three rounds of qualitative coding (open, axial, and selective coding). The results reveal the formation of a Transcendental Ethical Reputation Model based on authenticity, namely the alignment between verbal expression and reality in actual behavior (Q.S. Ash-Shaff: 2–3). Based on the analysis, four typologies of approach styles were identified: Spiritual Branding (Q.S. Fatir: 10), Humility-Based Branding (Q.S. Al-Furqan: 63), Gentle Power (Q.S. Ali Imran: 159), and Claim to Authority based on Respect (Q.S. Al-Hajj: 30). This model is reinforced by the triadic persuasive communication method (Q.S. An-Nahl: 125) in conjunction with (Q.S. At-Taubah: 105) to build social proof and affirm superiority (Q.S. Al-Qashash: 26). Theoretically, this model represents a radical improvement upon Erving Goffman’s theory of impression management while simultaneously complementing and offering a theocentric (ahsan taqwim) alternative paradigm to Abraham Maslow’s theory of self-actualization (Q.S. At-Tin: 4) and Albert Bandura’s description of self-efficacy (Q.S. Ali Imran: 139), which has implications for the resilience of an individual’s psychological dignity (Q.S. Al-Baqarah: 273).